Internal Construction Relationship With Quality Of Drinking Water On The Drinking Water Depot In Pemalang District - Casmitun Casmitun; Yani Kamasturyani; Lili Amaliah (Jurnal Kesehatan Mahardika, 2020)
Preliminary; Internal Supervision on Drinking Water Depots is needed to improve DAM sanitation hygiene in accordance with Minister of Health Regulation No.43 / 2014 and improve the quality of drinking water quality in reducing diseases due to contamination of drinking water (according to drinking water quality standards RI Permen 32 number 2017). In Pemalang District in 2017 34.2% of the 120 positive coliform bacteria samples, the results of Sanitation Inspection obtained 46.68% Not Fulfilling HealthyRequirements. Aim; Knowing the relationship between internal supervision and the quality of drinking water depots in Pemalang District. Method; descriptive correlation with cross sectional approach. The study sample was 57 respondents using total sampling. The research instrument used was an internal supervision questionnaire and an internal supervision checklist for sanitation hygiene attachment II Permenkes Number 32 of 2017. Statistical tests were carried out by test chi square. This research was conducted in Pemalang District in January - February 2019. Results; The research shows that the internal control indicators according to CR% 70 - 100 procedures have 29 respondents (50.88%) while the Indicators do not fit the CR% procedure below 70 there are 28 respondents (49.12%). The quality of drinking water in DAM is known to be 49.12% which does not meet the requirements. Statistical test results with chi square the value of p = 0,000 is smaller than the value of α = 0.5, Conclusion; the relationship between internal supervision and the quality of drinking water depots in Pemalang Sub-district is stated.